Bertahan dan Bersaing di Tengah Disrupsi: Mekanisme Survival Pedagang Pasar Tradisional Wonokromo Menghadapi Pasar Retail Online - Istiarohmi, Luluk (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2024)
The emergence of online markets has accelerated social transformation within society, particularly in consumption patterns shifting from conventional to digital modalities. This phenomenon has posed a new challenge for traditional market traders. While some traders are able to adapt by marketing their goods online, the limitations faced by Wonokromo Traditional Market traders force them to survive with only the limited resources they have. This research aims to identify survival mechanisms utilized by traditional market traders in response to the proliferation of online stores. The study employs a qualitative method with a phenomenological approach. Findings from this study indicate that the economic conditions of Wonokromo Traditional Market traders are highly unstable, and they sustain themselves through very limited mechanisms, such as welcoming customers warmly, maintaining consistency in trade, clearing out old stock, avoiding market trends, and strengthening solidarity among traders.